Growth performance of nursery pigs fed BIOSAF yeast, alone or in combination with an in-feed antimicrobial - B M Hildabrand; T E Burkey; K A Skjolaas-Wilson; B J Johnson; J Ernest Minton; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2005)
A total of 280 pigs were used in a 28-d growth study to evaluate the effects of feeding the antimicrobial carbadox, BIOSAF (0.4%), and the combination of carbadox and BIOSAF yeast (0.15%) in nursery pig diets. Over the length of the entire trial, pigs fed the diet containing carbadox alone had greater ADG than did pigs fed the control diet or the diet containing 0.4% BIOSAF. Overall, pigs fed the diet containing both carbadox and 0.15% BIOSAF had greater ADG than did pigs fed the control diet or the diet containing 0.4% BIOSAF (P<0.04), although their growth performance did not differ from that of pigs fed carbadox alone. Antibody titers in response to routine vaccination against Mycoplasma hyopneumoniae were not affected by dietary treatment. There was no evidence that BIOSAF improved growth performance of nursery pigs, either alone or in combination with the carbadox. It is possible that the interactive effects of BIOSAF that have been reported for other in-feed antibiotics are not present when BIOSAF is combined with carbadox, or perhaps interactive effects are only observed when carbadox itself exerts a more potent stimulation of ADG in nursery pigs.; Swine Day, 2005, Kansas State University, Manhattan, KS, 2005
Keywords: Swine day; 2005; Summary Publication of Report of Progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 964; Kansas Agricultural Experiment Station contribution; no. 06-63-S; Antimicrobials; BIOSAF; Carbadox; Nursery pig; Pigs; Swine